Effects of different levels of chili straw supplementation on growth performance, rumen fungal community structure, function and economic benefits in sheep - Li, Jinlong; Xu, Congbin; He, Linjiao; Tuo, Yong; Yang, Yuxia; Ma, Yan; Guo, Tongjun (Frontiers in Microbiology, 2025)
Chili straw is a crop residue that can be used as an unconventional feed additive in animal production, exhibiting potential value in improving animal health. This study investigated the effects of dietary chili straw on growth performance, rumen fungal community composition, and metabolic function in sheep. Thirty finishing sheep (3-4 months old) with similar body weights were randomly divided into three groups (n = 10) and fed diets containing 0, 10, and 20% capsicum straw (CS) for 63 days, including a 7-day adaptation period. At the end of the trial, body weights were recorded, and rumen fluid samples were collected to assess growth performance, fungal diversity, and functional profiles. Dry matter intake (DMI) significantly increased in the 10% CS group (P < 0.01), which was 9.71% higher than that of CON group, while DMI and final body weight of 20% CS group (P < 0.01 or P < 0.05) decreased by 6.81 and 8.81%, respectively, compared with CON group. Final body weight and average daily gain (ADG) showed an upward trend in the 10% CS group (P > 0.05), while ADG displayed a downward trend in the 20% CS group (P > 0.05). The ACE and Chao1 indices were significantly elevated in the 20% CS group (P < 0.05). Principal coordinate analysis (PCoA) and non-metric multidimensional scaling analysis (NMDS) showed that compared with the control (CON) group, the representative points of the 20% CS group gathered more closely. Relative abundances of Ascomycota and Cladosporium increased, whereas Basidiomycota and Kazachstania decreased in CS-supplemented groups (P > 0.05). FUNGuild functional prediction indicated increased relative abundances of symbiotrophic and pathotrophic fungi and decreased saprotrophic fungi in CS groups (P > 0.05). The gross profit and net profit of the CS10% group were significantly higher than those of the other groups, which were 15.16 and 24.44% higher than those of the control group, respectively. Thus, adding 10% CS to sheep feed can improve the composition of rumen fungi and growth performance, thereby increasing profitability in sheep production.